2015
DOI: 10.1016/j.chemgeo.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous growth of cadmium and cobalt carbonate phases at the 101¯4 calcite surface

Abstract: The ability of surface precipitates to form heteroepitaxially is an important factor that controls the extent of heterogeneous growth. In this work, the growth of cadmium and cobalt carbonate phases on 1014 calcite surfaces is compared for a range of initial saturation states with respect to otavite (CdCO 3 ) and sphaerocobaltite (CoCO 3 ), two isostructural metal carbonates that exhibit different lattice misfits with respect to calcite (−4% and −15%, respectively, based on 1014 surface areas). Calcite single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 60 publications
4
19
1
2
Order By: Relevance
“…The misfits between the overgrowths and the substrates can also explain the different formation behavior observed in the otavite/dolomite and otavite/calcite systems and in the spherocobaltite/dolomite and spherocobaltite/calcite systems. As explained above, when otavite grows on calcite, it shows a preferential orientation along the [42.1] direction, 13,16 whereas on dolomite, otavite does not have any preferential orientation. Growing on calcite, the otavite structure has to expand to accommodate the deformation, leading to misfits of 1.42% and 3.05% for the [01.0] and [42.1] directions, respectively.…”
Section: Crystallographic Features Of the Dolomite (104)mentioning
confidence: 93%
See 1 more Smart Citation
“…The misfits between the overgrowths and the substrates can also explain the different formation behavior observed in the otavite/dolomite and otavite/calcite systems and in the spherocobaltite/dolomite and spherocobaltite/calcite systems. As explained above, when otavite grows on calcite, it shows a preferential orientation along the [42.1] direction, 13,16 whereas on dolomite, otavite does not have any preferential orientation. Growing on calcite, the otavite structure has to expand to accommodate the deformation, leading to misfits of 1.42% and 3.05% for the [01.0] and [42.1] directions, respectively.…”
Section: Crystallographic Features Of the Dolomite (104)mentioning
confidence: 93%
“…Our observations of spherocobaltite growing on dolomite surfaces contrast with the previously reported formation of an amorphous Co-bearing hydroxy-carbonate phase on calcite (10.4) surfaces. 16 The formation of different phases on dolomite and calcite (10.4) surfaces from Co-bearing solutions can be due to both the different supersaturations with respect to the spherocobaltite in the solutions and the different substrates used. As in the case of otavite, spherocobaltite lattice parameters were estimated on the high-resolution images ( Figures 3C and S5, Supporting Information).…”
Section: Spherocobaltite Growth On Dolomite (104) Sur-facementioning
confidence: 99%
“…Показано, в частности, что двухвалентные катионы металлов в одном случае образуют поверхностные гидратированные комплексы, в другом -проникают в решетку кальцита с образованием поверхностных слоев карбонатов. В недавних работах (Xu et al, 2017;Xu et al, 2015) показано, например, что при адсорбции Mn 2+ , Cd 2+ из водного раствора на поверхности CaCO 3 (1014) образуется ИССЛЕДОВАНИЕ ВЗАИМОДЕЙСТВИЯ АТОМОВ Co, Mn, Fe С КАЛЬЦИТОМ МЕТОДОМ РЕНТГЕНОВСКОЙ ФОТОЭЛЕКТРОННОЙ СПЕКТРОСКОПИИ структурно согласованный с подложкой упорядоченный тонкий слой карбонатов металлов, несмотря на несогласованность постоянных решеток подложки и адсорбата. Формирование таких упорядоченных структур происходит в результате релаксации напряжений при росте пленки из раствора и образовании твердых растворов на границе раздела, имеющих состав, отличающийся от термодинамически стабильных фаз соответствующих массивных материалов.…”
Section: Introductionunclassified
“…Особенность для кобальта заключается в том, что рост поверхностных соединений не происходит вдоль какого-либо кристаллографического направления. Это, по мнению авторов (Xu et al, 2015), свидетельствует о том, что твердый раствор (Са,Со)СО 3 на поверхности не образуется. Вместо этого происходит образование смешанной гидрокси-карбонатной кобальтовой фазы Co 2 (OH) 2 CO 3 на кальцитовом субстрате.…”
Section: Introductionunclassified
“…Recently, González-López et al [17] reported the thermochemistry of (Ca,Co)CO 3 solid solutions from density functional theory simulations and concluded that many Ca 1−x Co x CO 3 mineral solid solutions (with observed compositions of up to x = 0.027, and above x = 0.93) are metastable with respect to phase separation. Finally, Xu et al [18] studied the interaction of calcite with solutions with a very low Co 2+ concentration ([Co aq ] initial = 1-10 ppm) using AFM and XPS. They suggested that that the lattice misfit between CoCO 3 and CaCO 3 is too large to allow heteroepitaxial growth of a pure cobalt carbonate phase in ambient conditions.…”
Section: Introductionmentioning
confidence: 99%